(untitled) (Fiep Bulletin - online, 2011)
The project Arandu-Porã was idealized to act alongside the indian community Guarani Mbyá, located in the city of SP, in the protected reserve of Capivari-Monos, by the banks of the Billings. Dam. It has been contemplated in the II Public Selection of the Petrobrás Environmental Program in 2006. The project has as its general objective to promote the preservation and recovery of springs in the area currently occupied by the tribes as a way to improve its sustainability. It also wishes to develop a model center of environmental education in the preservation of springs in the Atlantic Forest, aiming the awareness of "non indians" who live in the vicinity and the stimulous of other indian communities in preserving their natural water sources. The project Arandu-Porã in its first year of life tried to reach and capacitate the local school teachers, the communitary agents and the indian and non-indian leaderships so that they could develop ways of action, methodologies and environmental projects in an articulated and interdisciplinary manner, centered in a bigger participation of all in the handling of their local enviroment. Another act of the project was to reach and capacitate the communitary leaderships and their communities to preserve the APA Capivari-Monos and the area of Protected fountainheads through the development of education, social inclusion and the creation of job and income alternatives, everything with the local sustainability in mind. Finally, it tries to stimulate the participation of the locals in the solution of socio-enviromental issues by pointing out the necessity of valorizing, creating and enlarging the proper use of public or private areas destined to the preservation of the biodiversity. In short, it fights the unnecessary waste of natural resources and the damaging environmental practices.